Assessment Of Biochar Properties Derived From Treated And Untreated Coconut Frond As A Potential Solid Fuel - Mohamad Aziz, Nur Syairah (2023)
This study is performed with the objectives of evaluating the properties of biochar produced from slow pyrolysis of coconut frond and to study the influence of feedstock pre-treatment on the properties of CF biochar. This research also aims to assess the potential of CF biochar and CF feedstock as a solid fuel by evaluating the properties of CF bio-briquette.